Remanufacturing authorization strategy for competition among OEM, authorized remanufacturer, and unauthorized remanufacturer - Zhou, Qin (2022)
Engaging authorized manufacturers (ARs) is a strategy that has been adopted by many original equipment manufacturers (OEMs) to compete with unauthorized remanufacturers (URs). As a result, new products, authorized remanufactured products, and unauthorized remanufactured products may coexist in the same market. The OEM needs to strategically determine whether to compete with the UR only through new products or to authorize another independent remanufacturer to compete with the UR. This paper examines a supply chain consisting of an OEM, an UR and an AR competing in the same market. We develop a game-theoretic model and investigate the equilibrium decisions for two scenarios: the unauthorized remanufacturing and authorized remanufacturing scenarios. In the unauthorized remanufacturing scenario, which only the OEM and the UR compete in the market, we derive the OEM's and UR's optimal production quantities and the UR's product quality. We find that the UR would always remanufacture at a high-quality level when the remanufacturing cost is low, and vice versa. In the authorized remanufacturing scenario, the AR remanufactures by cooperating with the OEM through an authorization fee contract. We find that (1) when the AR implements the authorization fee decision, a Pareto improvement region exists when the remanufacturing cost is low; (2) when the OEM implements the authorization fee decision, a Pareto improvement region exists when remanufacturing is lower than a given threshold; and (3) when neither the OEM nor the AR has the full bargaining power to make the authorization fee decision, the UR will benefit from an OEM with a stronger bargaining power. That is because the OEM's authorization fee decision will compromise the AR's competitiveness in the market, which benefits the UR. Finally, we extend the model to investigate whether the OEM should conduct remanufacturing as its optimal strategy.